2012
DOI: 10.1037/a0027388
|View full text |Cite
|
Sign up to set email alerts
|

Food for thought? Trust your unconscious when energy is low.

Abstract: Recent studies showed that a period of unconscious thought can help when making complex decisions. Under some circumstances, unconscious thought improves decisions even more than conscious thought. Executive functioning depends on energy provided by glucose, and we know from previous research that the performance of various conscious processes deteriorates when energy is low. Unconscious processes require less energy and may operate unhampered when energy is low. Therefore, we propose that whereas low blood gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
1
11
0
2
Order By: Relevance
“…This relative preference reflects how well participants differentiate between the best phone and the worst phone (Dijksterhuis, 2004). A 2 (cognitive style)  2 (thought condition) mixed analysis of variance (ANOVA) revealed no main effect of cognitive style (F(1,118) = 0.74, p > .05, g p 2 < .01), but a significant main effect of thought condition (F(1,118) = 4.63, p < .05, g p conscious thought (M = 14.7, SD = 18.3), consistent with previous findings (e.g., Bos et al, 2011Bos et al, , 2012Dijksterhuis, 2004;Ham et al, 2009;Hasford, 2014;Li et al, 2014). Most interestingly, we found a significant cognitive style  thought condition interaction (F(1,118) = 5.90, p < .05, g p 2 = .05; Fig.…”
Section: Resultssupporting
confidence: 89%
“…This relative preference reflects how well participants differentiate between the best phone and the worst phone (Dijksterhuis, 2004). A 2 (cognitive style)  2 (thought condition) mixed analysis of variance (ANOVA) revealed no main effect of cognitive style (F(1,118) = 0.74, p > .05, g p 2 < .01), but a significant main effect of thought condition (F(1,118) = 4.63, p < .05, g p conscious thought (M = 14.7, SD = 18.3), consistent with previous findings (e.g., Bos et al, 2011Bos et al, , 2012Dijksterhuis, 2004;Ham et al, 2009;Hasford, 2014;Li et al, 2014). Most interestingly, we found a significant cognitive style  thought condition interaction (F(1,118) = 5.90, p < .05, g p 2 = .05; Fig.…”
Section: Resultssupporting
confidence: 89%
“…Recently, psychophysiology has been at the junction of psychological and medical science, and its popularity and importance have expanded in proportion to the realization of the relationship between mind and body (Gross, Canteras, 2012;Bos, Dijksterhuis & Van Baaren, 2012;Fabiani, 2012). Within the framework of psychophysiology, certain areas are identified that are associated with the development of particularly important problems, among which psychophysiology is sensory -the psychophysiology of sense organs, sensations and perceptions; psychophysiology of the organization of movements; psychophysiology of activity; psychophysiology of arbitrary actions; psychophysiology of attention, memory and learning; psychophysiology of speech and thinking; psychophysiology of motivation and emotions; psychophysiology of sleep, psychophysiology of stress; psychophysiology of functional states and others (Greenland, Xenias & Maio, 2012;Kakarot, Mueller & Bassarak, 2012;Kircanski, Morazavi, Castriotta, Baker, Mystkowski, Yi & Craske,2012).…”
Section: Jpes ®mentioning
confidence: 99%
“…Second, we influence a biological mechanism of our participants directly (see limitations in Emanuele et al (2008); Koenigs and Tranel (2007); Sanfey et al (2003)). We do so in a way that represents a natural manipulation such as most customers are faced with every day (see limitations in Bos, Dijksterhuis, and van Baaren (2012); Crockett et al (2009)). sbr special issue 5/14 7-49 Third, we measure participants' reactions in an experimental setting that represents an important environmental influence, price fairness perception, on a selected construct in consumer behavior.…”
Section: Introductionmentioning
confidence: 99%